A Watershed Modeling Framework for Phosphorus Loading from Residential and Agricultural Sources. Issue 4 (1st July 2014) - Sinclair, Andrew; Jamieson, Rob; Madani, Ali; Gordon, Robert J.; Hart, William; Hebb, Dale
Abstract : Phosphorus (P) loading from residential onsite wastewater systems (OWSs) into neighboring surface waters is a poorly understood process in rural watersheds; this can be further challenged when rural residential dwellings are intermixed with agricultural land use. The objectives of this research were (i) to design a P onsite wastewater simulator (POWSIM) to assess P loads from individual or clusters of residential OWSs typically used in Nova Scotia, Canada; and (ii) to simulate OWS P loads in a mixed agricultural watershed (Thomas Brook Watershed [TBW], NS) using the Soil and Water Assessment Tool (SWAT) model in conjunction with POWSIM, to predict and compare P loading from agricultural and residential sources. The POWSIM loading tool has three computational components: (i) disposal field selection and treatment media mass calculation, (ii) disposal field P treatment dynamics, and (iii) soil subsurface plume P treatment dynamics. The combination TBW POWSIM and SWAT modeling approach produced a better simulation of baseflow total P (TP) loads in both a predominantly residential subcatchment and one dominated by agriculture than the SWAT model without POWSIM. The residential subcatchment had 48% of its average annual land use TP load (simulated) contributed by OWSs, whereas the agricultural subcatchment had 39%. Watershed‐scale sensitivity analyses of POWSIM input parameters for 18‐ and 50‐yr OWS operation periods found the P loading rate into the disposal field, long‐term P removal rates in the disposal field and soil systems, soil maximum P sorption capacity, and mass of native soil involved in P treatment to be most sensitive.